(untitled) (University of Khartoum Journal of Agricultural Sciences, 2021)
The aim of this note was to outline the processing of a table-salt, locally known as “Foulgo salt” in Gabal Marra area, and highlighting its socio-economic impact on the livelihood of the mountain dwellers. Salt samples were procured from a local producer and were chemically analyzed in the laboratory of the Soil and Environmental Sciences Department, Faculty of Agriculture, University of Khartoum in August 2020. The preparation steps include: impregnation of soil by salt in the farm, collection and percolation of the soil and evaporation of the solute at home and yield of the salt. The salt is grey to pale brown in colour and has small crystals and readily dissolves in water. The salt is composed of 78.9% NaCl, 0.5 % Ca, 0.78 % Mg and traces of K. Its Ec is 19.97dS/m and TDS of 1280.8 ppm. The salt is used for human consumption and for various purposes. It is sold to get income and historically it was used for trade both as commodity and exchange currency. The salt is still produced at small scale, and its production is anticipated to continue for some time in response to the prevailing local demand